POLARISASI BERITA BOHONG COVID-19 : VIKTIMISASI KOLEKTIF - Candra, Marli; Alifiana, Nada Fitriyah (Faculty of Law, Universitas Pasundan, 2021)
COVID-19 has changed the structural behavior of the world community, including the increasing spread of hoax. The massive spread of hoaxes and the abundance of available information has confused the community in indicating which information is correct or hoax. This paper uses a qualitative method with an analytical-descriptive approach. The author emphasizes the aspect of in-depth understanding of a problem by reviewing and analyzing scientific works and various scientific literature. The central factors of this research are facts related to the COVID-19 fake news and the identification of the impact of the spread of the false news. The study found that the huge number of hoaxes related to COVID-19 caused collective victimization, namely the community. Unclear information results in civil resilience. This resilience raised the community resistance regarding government policies in minimizing the impact of COVID-19 on public health in general. Keyword: COVID-19 Polarizattion; Hoax: Collective Victimization.